Cost-effectiveness analysis of hydrophilic-coated catheters in long-term intermittent catheter users in the UK. (1st February 2023) - Baker, Hannah; Avey, Brooke; Overbeck Rethmeier, Line; Mealing, Stuart; Lynge Buchter, Marie; Averbeck, Márcio Augusto; Thiruchelvam, Nikesh
Abstract: Objective: To estimate the cost-effectiveness of single-use hydrophilic-coated intermittent catheters (HCICs) versus single-use uncoated intermittent catheters (UICs) for urinary catheterization. Methods: The evaluation took a UK national health service (NHS) perspective. The population of interest were people using intermittent catheters, with either a spinal cord injury or multiple sclerosis. A Markov model was developed that estimated costs and clinical evidence over the lifetime of a hypothetical cohort and applied health-related quality- of- life estimates. Model inputs were sourced from published evidence, including a network meta-analysis to inform the treatment effect (reduction in catheter-associated urinary tract infections [CAUTIs]), and were supported by expert opinion. The model outputs included per-patient lifetime costs, quality-adjusted life years (QALYs), and the incremental cost effectiveness ratio (ICER). Event counts were also produced. Results: Using HCICs instead of UICs could prevent seven CAUTI events per patient over a lifetime horizon (1.8 requiring secondary care). Overall, lifetime use of HCICs is £3, 183 more expensive than use of UICs per patient. However, for these additional costs, 0.55 QALYs are gained. The ICER is £5, 755 per additional QALY gained. Key drivers of the model results were identified and subject to sensitivity analyses. The results were found to be robust to parameter uncertainty. Conclusion: HCICs are likely to be a cost-effective alternative to UICs, a result driven by substantial reductions in the number of CAUTIs. Their adoption across clinical practice could avoid a substantial number of infections, freeing up resources in the NHS and reducing antibiotic use in urinary catheter users. PLAIN LANGUAGE SUMMARY: A new economic model was developed from a United Kingdom National Health Service perspective, to explore whether hydrophilic-coated intermittent catheters would be "worth" introducing for intermittent catheter users with either a spinal cord injury or multiple sclerosis. More specifically, costs were analyzed alongside clinical evidence and health-related quality-of-life data to investigate whether hydrophilic-coated intermittent catheters would offer a notable health benefit when compared with uncoated intermittent catheters for the assessed population, whilst keeping costs to the National Health Service sufficiently low. Model inputs were sourced from published evidence where possible, and experts were consulted otherwise. The results showed that, whilst lifetime use of hydrophilic-coated intermittent catheters is £3, 183 more expensive than use of uncoated intermittent catheters per patient, the health benefit with hydrophilic-coated intermittent catheters offsets these costs, by definition a cost-effective result. This means that hydrophilic-coated intermittent catheters are likely to be a cost-effective alternative to uncoated intermittent catheters. Their adoption across clinical practice could avoid a substantial number of infections, thereby freeing up healthcare resources in the National Health Service and reducing antibiotic use in urinary catheter users.